DE WINTER'S SIGN AS ELECTROCARDIOGRAPHIC EQUIVALENT OF STEMI INFARCTION - Vukićević, Verica; Ilic, Andrijana; Mirkovic, Olja; Jankovic, Tamara (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Introduction: We present the rarity early recognition and management of De Winter's ECG pattern at the prehospital level.Case report: A 68-year-old man felt chest pain with propagation in both arms and back, followed by nausea and vomiting. Conscious, pale, cold sweaty, agitated, normofrequency, normotensive. ECG: sinus rhythm 70/min, negative T in D3 and aVF. Reduced r in V2-V4, concomitant ST depression in V3-V5 with high, symmetrical T in V2-V5. A prehospital working diagnosis was De Winter T/ST pattern. After placement of 2 intravenous cannulas, prescribed drug therapy, with monitoring of vital functions and an announcement of arrival, he was transported directly to the catheterization room. The diagnosis was confirmed by an interventional cardiologist and a stent was implanted.Conclusion: Failure to recognize De Winter's sign as a STEMI equivalent can lead to a delay in activation of the STEMI network and sometimes be fatal to the patient.
Keywords: electrocardiographic record, STEMI infarction, De Winter's sign